Optimization of Groundnut Oil Extraction using Chemical Method - Mari, H. H.; Mustapha, N.; Mohammed , I.; Mohammed , H. D.; Kiman, S; Ngulde, A. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The chemical extraction technique is associated with suboptimal oil yield and quality, necessitating the development of optimized extraction technique. In this study, groundnut oil was extracted chemically with n-hexane using the Response Surface Methodology (RSM) and the extraction process was optimized considering the hexane concentration (30, 40 and 50), extraction duration (3, 5, 7 hrs) and the amount of groundnut (15, 20, and 25 g) as factors and the oil yield was evaluated. The Fourier Transform Infrared (FTIR) technique was used to check at the functional groups on the extracted oil. In the experimental results, the average optimum values of extraction time, solvent amount, groundnut amount, and oil yield were 5.05 hr, 40.5 mL, 20.25 g, and 48.18%, respectively. The profiled extracted oil by FTIR showed peaks at 3452 cm-1 2969 cm-1 2712 cm-1 1763 cm-1 1474 cm-1 which indicates the existence of -CH and OH, CH, C-H, aldehydes, ketones, carboxylic acids, and methylene groups functional groups which are useful for determining the oil’s quality. Furthermore, findings from this study showed that RSM-optimized process parameters result in significantly greater oil yields than conventional approaches.